EFFECT OF HYDROPHILIC POLYMER IN THE RELEASE PATTERN OF TERBUTALINE SULPHATE TRANSDERMAL PATCH - Maharjan, Ruby (Journal of Drug Delivery and Therapeutics, 2014)
The aim of the study is to formulate matrix based transdermal patch for water soluble drug like terbutaline and to study the effect of formulation composition on physical property, to study permeation profile of the patches through hairless mice skin and to study release profile of the patches. Five monolayered terbutaline sulphate transdermal patches bearing a rate controlling membrane were prepared by solvent-casting technique. Five formulations were prepared with varying concentrations of sodium alginate- FI, FII, FIII, FIV and FV with 350mg, 450mg, 250mg, 400mg and 300mg respectively. The 15mg terbutaline sulphate, 0.5ml glycerine and 0.1% chlorocresol were used along with sodium alginate in preparation of drug matrix. A mixture of ethylcellulose, chloroform and dichloromethane were used for preparation of rate controlling membrane using dibutylphthalate as a plasticizer. The physicochemical characteristics of the patches were evaluated by standard techniques. In-vitro drug release test was done in Keshary Chein diffusion cell by using skin of albino mice for 6 hours study. From the in-vitro permeation release study, formulation FII, FIV and FV followed Higuchi order kinetics while FI followed Peppas equation and FIII followed first order kinetics. Formulation FII showed more permeability than other formulations due to high concentration of sodium alginate in the FII. Thus the release of drug was found to be directly related to the concentration of SA.